Using games to support collective action in the real world - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
The use of economic games in the field to explore how people's decisions affect individual and collective well-being has increased over the last few years as a tool to study economic behavior (Table 1). There are a number of applications of these games to issues of development and the environment, with quite a number of these addressing particular aspects of collective action such as cooperation, voluntary contributions to public goods, trust, reciprocity, altruism, and social norms.